ANALISIS PERBANDINGAN SISTEM TRADISIONAL DENGAN SISTEM ACTIVITY BASED COSTING DALAM PERHITUNGAN HARGA POKOK PRODUKSI DI PT. PINDAD (PERSERO) - Agustami, Silviana (Jurnal Riset Akuntansi dan Keuangan, 2014)
Calculation of cost of good manufactured (COGM)Â  is amount of all cost production used for processing raw materials into finished good in current period. Uncorrect calculation of COGM will give unfavorable effects for the company, because COGM has a function as basis for deciding the price and profit. This research used descriptive comparative design, which compares two variabels (Traditional System and Activity Based Costing [ABC]). Nazir (2004) mentioned that descriptive research makes sistematically ilustration about the observing phenomena. According to Sugiyono (2002), comparative research is a research that comparing two or more variable. Researcher did this research at PT. Pindad, Jl. Jend. Gatot Subroto 517 Bandung. PT. Pindad uses traditional system to calculate COGM, that is the reason for researcher to do this research. The research did from 2013, December untul 2014, January. The result of this research shows difference between traditional system and ABC system; COGM average of traditional system is lower than the ABC system. It means that COGM calculate uses ABC system give higher value than uses traditional system though the difference value was not too far.